Governança de risco em barragens de contenção de rejeitos: uma análise da lei de segurança de barragens e das entidades reguladoras - PEREIRA, Oniwendel Felipe de Morais (Universidade Federal do Pará, 2023)
Still in the first decade of implementation of the Dam Safety Law (LSB), three failures were recorded in Brazil in tailings containment dams with considerable socioeconomic and environmental impacts. These disruptions, at the beginning of the implementation of the LSB, draw attention to this important regulatory framework that should guarantee adequate Risk Governance and promote Brazilian society to support the strengthening of dam safety. In addition, observing other scenarios, such as the important region of the Amazon, where the State of Pará is located, one can observe a fact that reinforces the need to reflect on the safety of these structures, given that, according to SNISB data (ANA, 2021) is the second entity of the federation with the most dams for containing mining tailings, second only to Minas Gerais. Many concerns can be raised regarding the safety of these dams, one of them is a basic aspect, where the question is, does LSB present Risk Governance? And if it does, at what level is it present? Thus, this thesis aimed to analyze whether the LSB can be considered as having a low level of presence of Risk Governance and for this purpose, the hypothesis was formulated that a gap that exists in the LSB, tending to impair the safety of containment dams of tailings in Brazil, is caused by the adoption of a model with a low degree of Risk Governance. The question that guided the research hypothesis was: In comparison with the Risk Governance model developed by the IRGC (2017), as well as other models, can LSB be classified as low grade in terms of the presence of Risk Governance? The analysis was carried out by performing the structured comparison of the LSB with other models and to optimize this process, the Comparative Qualitative Analysis tool was used, through its variant Fuzzy Set QCA (fsQCA). Eight different cases were used as a basis for comparison and for the construction of causal conditions, the IRGC Risk Governance model (2017) was used. The results denied the hypothesis of this thesis, however, they contributed with final considerations relevant to the theme. Among them, it is noteworthy that most public entities that apply the LSB do not have full presence of Risk Governance in their regulatory frameworks, including SEMAS-PA, which only recently sought to start applying the LSB.